Radość (gaudium) w nauczaniu św. Augustyna - Eckmann, Augustyn (Vox Patrum, 2012)
Notes of St. Augustine on joy (gaudium) are based on both the philosophical tradition and the Bible. Bishop distinguishes the true joy from the false one. These two types of joy differ in the subject of happiness and its quality. True joy is purely spiritual (gaudium spiritale), aimed to eternal life, while the false joy turns to the worldly possessions. In this life is possible the joy that comes from hope (gaudium de spe), a real joy (gaudium de re) meet only in the future life. Everyday joy, which is consistent with reason and truth, leads to the eternal joy. The true joy arises when one attains the highest goal. It meets in God and is permanent.